2020
DOI: 10.1093/jnci/djaa040
|View full text |Cite|
|
Sign up to set email alerts
|

Contribution of Germline Predisposition Gene Mutations to Breast Cancer Risk in African American Women

Abstract: Background The risks of breast cancer in African American (AA) women associated with inherited mutations in breast cancer predisposition genes are not well defined. Thus, whether multigene germline hereditary cancer testing panels are applicable to this population is unknown. We assessed associations between mutations in panel-based genes and breast cancer risk in 5054 AA women with breast cancer and 4993 unaffected AA women drawn from 10 epidemiologic studies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 63 publications
5
58
0
Order By: Relevance
“…The mutant genes included BRCA1 published literature with germline sequencing data of large sample size. Therefore, we compared six frequently mutated genes between our Chinese cohort with published Caucasian 34 and African-American 35 cohorts. Comparing results are showed in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The mutant genes included BRCA1 published literature with germline sequencing data of large sample size. Therefore, we compared six frequently mutated genes between our Chinese cohort with published Caucasian 34 and African-American 35 cohorts. Comparing results are showed in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, this correlation was not confirmed in subsequent studies [ 90 ]. More recently, mutations in RECQL emerged as a moderate risk factor for BC in a cohort of African American women, indicating that mutations in the RECQL gene confer a moderate risk of BC [ 91 ]. These conflicting correlations could be explained by penetrance variability due to the consequences of the different types of the identified variants on the protein function and to the investigated cohorts belonging to different ethnicities [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some BRCA1 and BRCA2 mutations that are inherited increase breast cancer risk in women. Together, mutations in the BRCA1 and BRCA2 genes contribute to about 20–25% of inherited breast cancers [ 107 ]. In addition, genetic testing of breast cancer patients revealed that the population which is of African or Bahaman decent showed higher frequencies of BRCA1 and BRCA2 mutations [ 108 ].…”
Section: Influence Of Genetic and Epigenetic Factors On Breast Canmentioning
confidence: 99%
“…In addition, genetic testing of breast cancer patients revealed that the population which is of African or Bahaman decent showed higher frequencies of BRCA1 and BRCA2 mutations [ 108 ]. AA women carrying mutations in the PALB2, RAD51C, and RAD51D genes are more susceptible to ER-negative breast cancer [ 107 ]. Like BRCA1 and BRCA2 gene mutations, PALB2 mutations are also associated with high risk of breast cancer.…”
Section: Influence Of Genetic and Epigenetic Factors On Breast Canmentioning
confidence: 99%
See 1 more Smart Citation